Efek penambahan oats pada formulasi cookies gandum dilihat dari karakteristik fisik dan sensorinya - Monika Rahardjo; Ristia Widi Astuti; Dhanang Puspita; Monang Sihombing (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
This research aims to determine the effect of oats addition in wheat cookies formulation seen from physical and sensory characteristics. Six formulations used in this research consist of wheat flour and oats mixture namely Control (100%:0%), Formulation 1 (80%:20%), Formulation 2 (60%:40%), Formulation 3 (40%:60%), Formulation 4 (20%:80%), and Formulation 5 (0%:100%). Based on analysis of variance result at α = 5%, there was a significant difference in the value of hardness and work from control and all variation of cookies’ formulation. It was also found that the decreasing composition of wheat flour and increasing composition of oats caused a decrease in the value of hardness and work. The addition of oats in the formulation of wheat cookies increases the level of brightness (L), decreases the value of a* (red tone), and increases the value of b* (yellow tone) of cookies. From sensory evaluation, compared to controls, the addition of oats in the formulation increased the acceptance rating for color parameter for all formulation, taste parameter for Formulation 2 until 5, and overall parameter for Formulation 2 and 3, while for the texture parameter, the addition of oats did not provide an increased in the acceptance rating.